Socratic Method, the Violence of Questioning and Self-Knowledge in Teaching Philosophy - Šimenc, Marjan (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
In his work, Rudi Kotnik focuses on the self-knowledge of students and connects the didactics of philosophy with Gestalt therapy. In this paper, we discuss the question of whether the Socratic method offers the possibility of including self-knowledge in the teaching of philosophy. In doing so, we follow Kotnik's example and, in analyzing the use of the Socratic method in the teaching of philosophy, rely on its use in cognitive therapy. This connection opens up a whole range of insights. It turns out that Socratic questioning can act violently and arouse student resistance. However, if the method is used within a pedagogical relationship based on student acceptance, it can help students explore their experience and contribute to self-awareness.